Hereditary cardiac amyloidosis associated with the transthyretin Ile122 mutation in a white man. Issue 3 (1st September 1999) - Gillmore, J D; Booth, D R; Pepys, M B; Hawkins, P N
Abstract : An 83 year old white man with atrial fibrillation was admitted to hospital after a cerebral infarct. Echocardiography was characteristic of cardiac amyloid deposition and subsequent tests confirmed amyloidosis of transthyretin (TTR) type, in association with the Ile122 mutation of the TTR gene; this has only been reported previously in African Americans in whom it occurs with an allele frequency of 2%. Haplotype analysis did not suggest a different founder than for the African Ile122 mutation. Cardiac amyloidosis should be considered among elderly patients presenting with cardiac failure and/or arrhythmia, particularly if they are resistant to conventional treatment; if confirmed, it should be followed by precise characterisation of amyloid fibril type. The prevalence of autosomal dominant cardiac TTR amyloidosis in elderly white people is unknown but early diagnosis and supportive treatment may prevent complications among affected family members.